Childhood infections and asthma: at the crossroads of the hygiene and Barker hypotheses - Weiss Scott T; Tantisira Kelan G (Respiratory Research, 2001)
Abstract The hygiene hypothesis states that childhood asthma develops as a result of decreased exposure to infectious agents during infancy and early childhood. This results in the persistence of the neonatal T helper lymphocyte 2 immunophenotype, thereby predisposing the child to atopic disease. While multiple studies support the hygiene hypothesis in asthma ontogeny, the evidence remains inconclusive; multiple other environmental exposures in early childhood also alter predisposition to asthma. Moreover, the current paradigm for asthma development extends far beyond simple childhood environmental exposures to include fetal development, genetic predisposition, and interactions of the developmental state and genetics with the environment.